2017
DOI: 10.1590/1806-9061-2016-0275
|View full text |Cite
|
Sign up to set email alerts
|

Breed and Sex Differences in the Gross Anatomy, Digesta pH and Histomorphology of the Gastrointestinal Tract of Gallus Gallus Domesticus

Abstract: A study was conducted to investigate the influence of breed and sex in the gross anatomy, digesta and histology of Ross 308 broiler and Venda chickens. Chickens were slaughtered at 90 days of age and the pH of the digestive organs was measured immediately after slaughter.The digestive organ weights and lengths of Ross 308 broiler and Venda chickens were measured. Tissue samples of the duodenum, ileum and jejunal from each treatment group were collected and histologically examined. Higher (p<0.05) gizzard pH va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…All the above mentioned may explain why chickens, fed with the diet lower in ME and CP, showed greater relative weight of the crop, gizzard and pancreas. Mabelebele et al [ 23 ] reported that digestive organs in male chickens are heavier and longer than in females, which can result in greater production of digestive enzymes and a greater contact surface for the absorption of nutrients, and result in a higher rate of growth. In the present experiment, the females had greater relative empty weight of the proventriculus, gizzard and caeca, greater relative weight of the liver and pancreas as well as greater relative length of the small intestine and caeca.…”
Section: Discussionmentioning
confidence: 99%
“…All the above mentioned may explain why chickens, fed with the diet lower in ME and CP, showed greater relative weight of the crop, gizzard and pancreas. Mabelebele et al [ 23 ] reported that digestive organs in male chickens are heavier and longer than in females, which can result in greater production of digestive enzymes and a greater contact surface for the absorption of nutrients, and result in a higher rate of growth. In the present experiment, the females had greater relative empty weight of the proventriculus, gizzard and caeca, greater relative weight of the liver and pancreas as well as greater relative length of the small intestine and caeca.…”
Section: Discussionmentioning
confidence: 99%
“…On d 14 and 42, after 10 h fasting and free access to feed, four birds with BW within one standard deviation of the mean treatment weight were slaughtered humanely and chilled at 4°C for 12 h. The influences of gender were not determined on the studied parameters. To determine weights of carcass and metabolically active organs (liver, heart, pancreas, whole gut and its segments) and tissues (breast and thigh muscles), abdominal cavities of all carcasses were opened and then, they were carefully removed and weighed after its contents were cleaned [ 12 , 17 ]. The small intestine was carefully dissected from the mesentery and divided into its segments as duodenum, jejunum and ileum [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Digestive tract of the vertebrates varies anatomically as well as physiologically among the different species. Even among the bird species, variation in length and weight of small intestine does exist (Mabelebele et al, 2017). Similarly, anatomical topography of the crop rigorously depends on species (Kierończyk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%